ARTIFICIAL INTELLIGENCE AND AUTOMATION IN ACCOUNTING (American Journal of Interdisciplinary Research and Development, 2025)
This article examines the transformative role of artificial intelligence (AI) and automation technologies in modern accounting. Rapid developments in machine learning, robotic process automation, and intelligent data-processing systems have significantly improved the accuracy, speed, and efficiency of accounting workflows. The study analyzes the impact of AI-driven tools on financial reporting, auditing, cost optimization, and risk management.